Fully human recombinant antibodies against EphA2 from a multi-tumor patient immune library suitable for tumor-targeted therapy - Yaqi Yang (Taylor & Francis Group, 2021)
Enhanced EphA2 expression is observed in a variety of epithelial-derived malignancies and is an important target for anti-tumor therapy. Currently, Therapeutic monoclonal antibodies against immune checkpoints have shown good efficacy for tumor treatment. In this study, we constructed an immune single-chain fragment variable (scFv) library using peripheral blood mononuclear cells (PBMCs) from 200 patients with a variety of malignant tumors. High affinity scFvs against EphA2 can be easily screened from the immune library using phage display technology. Anti-EphA2 scFvs can be modified into any form of recombinant antibody, including scFv-Fc and full-length IgG1 antibodies, and the recombinant antibody affinity was improved following modification. Among the modified anti-EphA2 antibodies the affinity of 77-IgG1 was significantly increased, reaching a pmol affinity level (10−12). We further demonstrated the binding activity of recombinant antibodies to the EphA2 protein, tumor cells, and tumor tissues using macromolecular interaction techniques, flow cytometry and immunohistochemistry. Most importantly, both the constructed scFvs-Fc, as well as the IgG1 antibodies against EphA2 were able to inhibit the growth of tumor cells to some extent. These results suggest that the immune libraries from patients with malignant tumors are more likely to screen for antibodies with high affinity and therapeutic effect. The constructed fully human scFv immune library has broad application prospects for specific antibody screening. The screened scFv-Fc and IgG1 antibodies against EphA2 can be used for the further study of tumor immunotherapy.